Representasi Ikigai dalam Anime Barakamon: The Representation of Ikigai in the Anime Barakamon - Rani Arfianty; Ivana Hutagalung; Syifa Anggitha Hasiany Silalahi; Dhea Ananda Ashila; Jessia Sarah Simanjuntak (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study examines how the concept of ikigai is represented in the anime Barakamon. Using a descriptive qualitative approach, the research analyzes various scenes and dialogues that portray the journey of the main character, Seishuu Handa, in discovering his true self after experiencing a career and emotional crisis. Data were collected through the identification of significant scenes, the transcription of dialogues, and thematic categorization based on the four main components of ikigai: personal enjoyment or interest, individual competence, contribution to society, and professional value potential. The findings reveal that Barakamon clearly depicts Handa's process of rebuilding his ikigai through his relationships with the villagers, self-reflection, and creative engagement in the art of calligraphy. Handa's changes in attitude and psychological development demonstrate that ikigai is dynamic, evolving through a series of experiences, failures, and social interactions. This study concludes that Barakamon provides a compelling representation of how ikigai emerges in everyday life while highlighting the relationship between Japanese cultural values and the contemporary search for meaning in life.